Prediction of preeclampsia by uterine artery Doppler velocimetry between 16-28 weeks - Vibala A., Shantha; M., Mohanapriya; V. H., Vanitha Rukmani; M., Thamaraiselvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Prediction of preeclampsia by uterine artery Doppler velocimetry helps in reducing perinatal, maternal mortality and morbidity by individualizing treatment methods and prophylactic measures to prevent preeclampsia. Methods: A study of 100 singleton pregnancies was conducted in a tertiary care centre and the study population was subjected to uterine artery Doppler study at 16 to 28 weeks, uterine artery pulsatility index, resistance index and persistence of diastolic notch was obtained and the outcome of preeclampsia was studied. Results: Out of 100 women, when uterine artery notching at 16-28 weeks alone was considered, 46.15% of women developed preeclampsia and detection rate increased upto 87.51% when RI>0.65 was also included along with uterine artery diastolic notching. Conclusions: This study concludes that uterine artery Doppler, being non -invasive can be included during routine sonography to identify patients at risk of developing preeclampsia.